2021
DOI: 10.1177/09636625211005249
|View full text |Cite
|
Sign up to set email alerts
|

The explanation of a complex problem: A content analysis of causality in cancer news

Abstract: Understanding causality is a critical part of developing preventive and treatment actions against cancer. Three main causality models—necessary, sufficient-component, and probabilistic causality have been commonly used to explain the causation between causal factors and risks in health science. However, news media do not usually follow a strict protocol to report the causality of health risks. The purpose of this study was to describe and understand how the causation of cancer was articulated on news media. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…A content analysis (Peng et al, 2021; Prosser, 2010) was conducted on the news articles. Through an inductive analysis of a subset (20%) of the articles, informed by the scoping review and discussions in the science communication field, the data extraction criteria were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A content analysis (Peng et al, 2021; Prosser, 2010) was conducted on the news articles. Through an inductive analysis of a subset (20%) of the articles, informed by the scoping review and discussions in the science communication field, the data extraction criteria were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have explored media portrayals of health research, spanning antimicrobial resistance (Catalan-Matamoros et al, 2019), genetic testing (Bubela and Caulfield, 2004) and diabetes treatments (Vehof et al, 2018). Concerns have been raised about the lack of accuracy of medical news reporting (Lewis et al, 2010), including the media's representation of causality in cancer (Peng et al, 2021), AI use in health research (Samuel et al, 2020) and prescription medicine (Prosser, 2010), and the under-reporting of potential risks and limitations (Condit, 2004). Concerns have also been raised about celebrities engaging in health communication, spreading misinformation about illnesses and encouraging dubious treatments (Caulfield and Fahy, 2016).…”
Section: Evidence-based Journalism Is Criticalmentioning
confidence: 99%
“…A review of recent studies on coverage of cancer in the media suggests a strong interest in examining the medical aspects of cancer, such as reporting on risk factors, protective behaviors, and accuracy of medical information [38][39][40][41][42][43]. Interestingly, it seems that the tendency to focus on the medical dimensions of cancer characterizes not only research on mass media coverage of cancer, but also the coverage itself [44].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one study examining cancer coverage in the USA reported that national medical institutions, including the National Cancer Institute (NCI) and medical schools at research universities, were frequently cited in cancer news ( 18 ). Recently, Peng et al ( 19 ) also found that medical institutions, healthcare providers, and scientists were the major sources providing evidence regarding the causality of cancer risk factors in cancer news from American newspapers. Besides, regarding news coverage on cervical cancer and HPV, physicians, government agencies, and medical institution such as the Centers for Disease Control and Prevention (CDC) were once again the primary sources providing helpful information to the journalists ( 20 ).…”
Section: Introductionmentioning
confidence: 99%